1984
DOI: 10.1038/bjc.1984.159
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype analysis of carcinogen-treated Chinese hamster cells in vitro evolving from a normal to a malignant phenotype

Abstract: Summary The relationship of cytogenetic changes with the acquisition of an indefinite life span in vitro, the ability of cells to grow in soft agar and their tumourigenicity in syngeneic animals has been studied in control, trans-7,8-dihydrodiolbenzo(a)pyrene and 7fl,8a-dihydroxy-9a,10a-epoxy-7,8,9,10-tetrahydrobenzo(a)-pyrenetreated secondary cultures derived from Chinese hamster embryonic lung. Karyotype analysis revealed a sequence of chromosome changes as the cells progressed through culture. Aneuploidy, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The most particular case was made by Sachs et al (52,53), who have distinguished ''E'' chromosomes for expression and ''S'' chromosomes for suppression of neoplastic transformation. Indeed, 11 studies on karyotypes of spontaneously, chemically, or simian virus 40 virus-transformed CH cells have identified one or both of the two most prominent transformation-specific aneusomies that we have identified here, i.e., trisomies 3 and 5, regardless of the carcinogen or strain of the animal used (47,48,(53)(54)(55)(56)(57)(58)(59)(60)(61). Three of these studies also reported prominent trisomies of chromosomes 8 (61), 9 (55), and 10 (48).…”
Section: Table 4 Latent Periods From Inoculation Of Nmu-transformed mentioning
confidence: 99%
See 2 more Smart Citations
“…The most particular case was made by Sachs et al (52,53), who have distinguished ''E'' chromosomes for expression and ''S'' chromosomes for suppression of neoplastic transformation. Indeed, 11 studies on karyotypes of spontaneously, chemically, or simian virus 40 virus-transformed CH cells have identified one or both of the two most prominent transformation-specific aneusomies that we have identified here, i.e., trisomies 3 and 5, regardless of the carcinogen or strain of the animal used (47,48,(53)(54)(55)(56)(57)(58)(59)(60)(61). Three of these studies also reported prominent trisomies of chromosomes 8 (61), 9 (55), and 10 (48).…”
Section: Table 4 Latent Periods From Inoculation Of Nmu-transformed mentioning
confidence: 99%
“…For example, Deaven et al (56) remained uncertain about ''the specific chromosome change hypothesis,'' because different ''nonrandom'' karyotypes were found in CH tumors in their lab and in others. Likewise, others remained undecided or unconfirmed, because no unique transformationspecific aneusomies were found (47,48,54,59,61). As a result some began to interpret transformation-specific aneuploidies as evidence for oncogenes (58,60,62).…”
Section: Table 4 Latent Periods From Inoculation Of Nmu-transformed mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many more primary transformants can be generated and analyzed per cost in vitro than in animals. Several studies have documented that stable, morphological transformation of CHE cells in vitro by chemical carcinogens correlates well with tumorigenicity (20,66,68,69).…”
mentioning
confidence: 99%
“…To meet these criteria we studied the chromosomes of Chinese hamster embryo (CHE) cells transformed in vitro, because transformation in vitro can be detected early, within 2 months after treatment (20,66) and thus about 5 months sooner than chemical carcinogenesis (67). In addition, many more primary transformants can be generated and analyzed per cost in vitro than in animals.…”
mentioning
confidence: 99%